Sistema de seguridad perimetral para mejorar performance de una red de datos empresarial - Grados Jiménez, Carlos Eduardo (2014)
In Chapter I, the introduction to the whole thesis, which is presented as problematic inter alia, objectives, variables which help us to the understanding of it is detailed._x000D_ In Chapter II, we proceed to describe the theoretical framework of the thesis which is useful to the growth and further development. The description of the physical and logical network equipment is performed. Within management, the way indicated as currently manages the network, showing its weaknesses, threats and risks._x000D_ In Chapter III, we proceed to describe the methodology to be developed by the thesis, since her achieve evaluate possible solutions and / or problems which are detailed, selecting samples and collecting data. In addition to the goals set by fixed security methodology._x000D_ This chapter IV, we proceed with the development of the methodology, where security policies were formulated, analysis and requirements, plus software tools for monitoring equipment and additional hardware needed to implement the management model also suggests . As well as, issues related to quality of service, disaster recovery and technical failures are taken; and patterns of how the system will overcome them is established._x000D_ As the final part of Chapter IV discusses the implications for the future management model standard that is proposed to be developed in the company, ie how this model will ensure the scalability of both the management model, and hardware and software network so that they continue to meet the standards required by the company under its technological and organizational requirements._x000D_ In the last chapter, Chapter V and VI the results, conclusions and suggestions obtained with the development of this project is elaborated